"شهادة الزور في قانون العقوبات الأردني والمصري : "دراسة تحليلية مقارنة - Mohammad M. Moh'd Alghlailat
Testimony is considered one of the most important and commonest means of giving proof in the criminal matters, because it is applied to the accidental occurrences suddenly taking place;while no prior preparation of facts is made by the concerned parties for establishing evidence. The problem of this research is that the Jordanian legislator did not state as a condition the occurrence of perjury before the court only,but it can also take place before the prosecutor , in addition to the possibility of taking place before an officer or a body that has the power to listen to witnesses put to oath.The Jordanian legislator does not consider oath taking as one of the elements of perjury as a crime, unlike what obtains in the Egyptian legislation, in which oath taking is considered one of the elements of the crime of perjury. It is also observed that the Jordanian legislator does not consider the insistence on the false testimony, both before the prosecutor or the court, as one of the elements of the crime of perjury,contrary to what the Egyptian legislation stipulates by considering the insistence on the false testimony as one of the elements of that crime. Thus, the provisions of the crime of perjury in the Egyptian penal code commensurate with the provisions of Islamic law. The researcher adopted the comparative and analytical method while carrying out his study in order to accomplish his goal- that is to answer the problem of the study that has been identified. Meanwhile, this study has come out with a number of results which include that testimony, generally , is one of the topics considered of paramount importance in criminal matters, because it is one of the most important evidences relied upon by the court in deciding the fate of the accused, and it is a condition to be fulfilled before punishing the witness for the offence of perjury committed in his testimony before a judiciary, whether it is before the prosecutor or the court, and whether it is preceded by oath taking or not. This study also urged the Jordanian legislator to consider the crime of perjury as a crime against the religion and not tampering with justice. That would be through the nullification of Article of the Penal Code(If the testimony takes place without oath taken by the witness, the punishment is cut half), which means that oath taking is considered one of the elements of the crime of perjury.